1335 A multi-disciplinary inter-continental collaboration to build capability in occupational health among health care professionals. (24th April 2018) - Naik, Inakshi; Mittal, Ashish; Nicholas, Robin; Seneviratne, Mahinda
Abstract : Retired, Johannesburg, Guateng, South Africa The interaction between community, environment and the workplace is crucial in the provision of basic health care services in low resource/low income countries. UN's Sustainable development Goals and strategies of agencies WHO and ILO and professional bodies such as ICOH and IALI have highlighted the need for capability building and integration in delivering the necessary services to these communities. However, health care professionals, including medical doctors and nurses undergo limited training in occupational health during their professional undergraduate education. A series of workshops for health care professionals to develop knowledge and basic skills in workplace hazard identification, assessment and control were conducted in India and Malaysia. The multi-disciplinary program involving occupational medicine, hygiene, ergonomics and hazard communication was delivered by a group of occupational health professionals from four different continents. Their time and resources were provided voluntarily and at no fee or charge for the local organisers. The workshops consisted primarily of interactive group work facilitated by skilled specialists sharing their international experiences together with demonstration of case studies by local experts. Diverse local health care workers shared the challenges faced and successes achieved. The success of these workshops has inspired the volunteers to explore the potential for developing a more sustainable 'academy' for capability building in basic occupational health. This model for a social enterprise in low resource countries through collaborating at international level will be outlined and discussed.